2017
DOI: 10.1021/acs.est.7b02523
|View full text |Cite
|
Sign up to set email alerts
|

Interactions, Transformations, and Bioavailability of Nano-Copper Exposed to Root Exudates

Abstract: Due to the potential for interactions between crop plants and engineered nanomaterials (ENMs), there is increasing interest in understanding the bioavailability and effects of ENMs released into soil systems. Here, we investigate the influence of root exudates on the fate of ENMs from a thermodynamic perspective. Nano isothermal titration calorimetry was applied to determine thermodynamic parameters for the interaction between nanocopper (nCu) and synthetic root exudate (SRE) and its components (including suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 58 publications
0
71
0
1
Order By: Relevance
“…Recent study conducted by Huang et al indicated synthetic root exudates can promote Cu NPs dissolution rate and increase the bioavailability of free Cu ion in the soil systems. [88] For different plants organic matter composition in rhizosphere, therefore their effects on metal based NPs are different. Judy et al [89] studied bioavailability of Gold NPs to plants indicating the differences in root exudates between wheat and tobacco resulted into different aggregation of Gold NPs, affecting their bioavailability to plants.…”
Section: Interaction With Plant Rootsmentioning
confidence: 99%
“…Recent study conducted by Huang et al indicated synthetic root exudates can promote Cu NPs dissolution rate and increase the bioavailability of free Cu ion in the soil systems. [88] For different plants organic matter composition in rhizosphere, therefore their effects on metal based NPs are different. Judy et al [89] studied bioavailability of Gold NPs to plants indicating the differences in root exudates between wheat and tobacco resulted into different aggregation of Gold NPs, affecting their bioavailability to plants.…”
Section: Interaction With Plant Rootsmentioning
confidence: 99%
“…[32] RE have also been shown to alleviate the toxicity of metal-based ENMs, due to complexation with harmful metals. [33,34] However, the ENMs in this study were either carbon based or likely insoluble in the experimental media. Thus, the RE-caused mitigation of ENMs' growth inhibitory effects was not likely to have been via toxic ion sequestration.…”
Section: Soybean Root Exudates Ameliorated Effects Of Ceo 2 Nps Mwcnmentioning
confidence: 86%
“…Significant reduction of CuO-NPs to Cu 2 S and Cu 2 O was also shown in maize during rootshoot-root translocation of CuO-NPs (Wang et al 2012). The reason behind the transformation of Cu(II) to Cu (I) in plants may be ascribed to the presence of reducing sugars which get transported from leaf cells to roots (Huang et al 2017;Servin et al 2017a).…”
Section: Biotransformation Of Cu-based Nps In Soilmentioning
confidence: 95%
“…Interaction of Cu-NPs with plant root exudates also influences the fate of Cu-NPs and magnitude of toxicity. Huang et al (2017) determined the thermodynamic parameters for the interaction of Cu-NPs (40 nm) with a mixture of synthetic root exudates (SRE) and its components such as sugars, amino acids, organic acids, and phenolic acids by nano isothermal titration calorimetry. The data revealed a strong binding constant (K d = 5.645 × 10 3 M -1 ) for Cu-NPs SRE interaction, however, the binding of Cu 2+ was found stronger but varied for individual SRE components (Huang et al 2017).…”
Section: Genotoxic and Cytotoxic Effectsmentioning
confidence: 99%